Characteristics of Arctic polar stratospheric clouds and as measured by airborne lidar - Kent, G. S.; Poole, L. R.; Mccormick, M. P. (1986)
Airborne lidar measurements of backscattering from polar stratospheric clouds (PSCs) obtained in January 1984 are examined. The flights, principal characteristics of the lidar system, and the meteorological conditions during the flights are described. The characteristics and conditions for the formation of PSCs and the optical characteristics of the clouds are discussed. The properties of the North Polar vortex and El Chichon stratospheric aerosol are studied. Variations in the aerosol optical properties with temperature and water vapor concentrations are analyzed and modeled using a model based on volcanic aerosols and water vapor concentration. The modeled and experimental backscattering-temperature relationship are compared and good correlation is observed at pressure levels of 100 and 70 mb.